Are you PEPped and PrEPped for travel? Risk mitigation of HIV infection for travelers. Issue 1 (December 2016) - Brett-Major, D.; Scott, P.; Crowell, T.; Polyak, C.; Modjarrad, K.; Robb, M.; Blazes, D.
Abstract The HIV pandemic persists globally and travelers are at risk for infection by the Human Immunodeficiency Virus (HIV). While HIV-focused guidelines delineate risk stratification and mitigation strategies for people in their home communities, travel issues are not addressed. In this review, direct and indirect evidence on HIV risk among travelers is explored. The burgeoning practice of employing pre-exposure prophylaxis (PrEP) with anti-retroviral therapy in the non-travel setting is introduced, as well as the more established use of post-exposure prophylaxis (PEP). Challenges in applying these lessons to travelers are discussed, and a new guidelines process is scoped and recommended.